NMR reaction monitoring in flow synthesis - Gomez, M. Victoria; de la Hoz, Antonio (Beilstein Journal of Organic Chemistry, 2017)
Recent advances in the use of flow chemistry with in-line and on-line analysis by NMR are presented. The use of macro- and microreactors, coupled with standard and custom made NMR probes involving microcoils, incorporated into high resolution and benchtop NMR instruments is reviewed. Some recent selected applications have been collected, including synthetic applications, the determination of the kinetic and thermodynamic parameters and reaction optimization, even in single experiments and on the μL scale. Finally, software that allows automatic reaction monitoring and optimization is discussed.
Keywords: expert systems; flow chemistry; microcoil; NMR probes

(untitled) - Fitzpatrick, D. E.; Battilocchio, C.; Ley, S. V. (ACS Cent. Sci., 2016)

(untitled) - Ley, S. V.; Fitzpatrick, D. E.; Myers, R. M.; Battilocchio, C.; Ingham, R. J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kobayashi, S. (Chem. – Asian J., 2016)

Microreactors in Organic Synthesis and Catalysis - Wirth, T. (Wiley, 2008)

(untitled) - Mark, D.; Haeberle, S.; Roth, G.; von Stetten, F.; Zengerlez, R. (Chem. Soc. Rev., 2010)

Handbook of Synthetic Photochemistry - Albini, A.; Germani, L. (Photochemical Methods, 2010)

(untitled) - Yoshida, J.-i.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Kise, N.; Mimura, R. (Tetrahedron: Asymmetry, 2007)

(untitled) - Glasnov, T. N.; Kappe, C. O. (Chem. – Eur. J., 2011)

(untitled) - Adamo, A.; Beingessner, R. L.; Behnam, M.; Chen, J.; Jamison, T. F.; Jensen, K. F.; Monbaliu, J.-C. M.; Myerson, A. S.; Revalor, E. M.; Snead, D. R.; Stelzer, T.; Weeranoppanant, N.; et al. (Science, 2016)

(untitled) - Yue, J.; Schouten, J. C.; Nijhuis, T. A. (Ind. Eng. Chem. Res., 2012)

(untitled) - Sans, V.; Cronin, L. (Chem. Soc. Rev., 2016)

NMR Spectroscopy. Basic Principles, Concepts, and Applications in Chemistry - Günther, H. (Wiley-VCH, 2013)

Encyclopedia of Magnetic Resonance - Haner, R. L.; Keifer, P. A. (Flow Probes for NMR Spectroscopy, 2009)
And references therein.

(untitled) - Fratila, R. M.; Velders, A. H. (Annu. Rev. Anal. Chem., 2011)

(untitled) - Zalesskiy, S. S.; Danieli, E.; Blümich, B.; Ananikov, V. P. (Chem. Rev., 2014)

(untitled) - Olson, D. L.; Peck, T. L.; Webb, A. G.; Magin, R. L.; Sweedler, J. V. (Science, 1995)

(untitled) - Kamberger, R.; Moazenzadeh, A.; Korvink, J. G.; Gruschke, O. G. (J. Micromech. Microeng., 2016)

(untitled) - Saggiomo, V.; Velders, A. H. (Adv. Sci., 2015)

(untitled) - Ehrmann, K.; Saillen, N.; Vincent, F.; Stettler, M.; Jordan, M.; Wurm, F. M.; Besse, P.-A.; Popovic, R. (Lab Chip, 2007)

(untitled) - Massin, C.; Vincent, F.; Homsy, A.; Ehrmann, K.; Boero, G.; Besse, P.-A.; Daridon, A.; Verpoorte, E.; de Rooij, N. F.; Popovic, R. S. (J. Magn. Reson., 2003)

(untitled) - van Bentum, P. J. M.; Janssen, J. W. G.; Kentgens, A. P. M.; Bart, J.; Gardeniers, J. G. E. (J. Magn. Reson., 2007)

High signal to noise ratio in low field NMR on chip: simulations and experimental results - Wensink, H.; Hermes, D. C.; van den Berg, A. (Int. Workshop Micro Electromech. Syst., 7th, Maastricht, Netherland, 2004)

Finite Element Method Magnetics - Meeker, D.

(untitled) - Gómez, M. V.; Reinhoudt, D. N.; Velders, A. H. (Small, 2008)

(untitled) - Krojanski, H. G.; Lambert, J.; Gerikalan, Y.; Suter, D.; Hergenröder, R. (Anal. Chem., 2008)

(untitled) - Sharma, M.; Janssen, G.; Leggett, J.; Kentgens, A. P. M.; van Bentum, P. J. M. (J. Magn. Reson., 2015)

Annual reports on NMR spectroscopy - Keifer, P. A. (Flow techniques in NMR spectroscopy, 2007)
And references therein.

(untitled) - Suryan, G. (Proc. - Indian Acad. Sci., Sect. A, 1951)

(untitled) - Sudmeier, J. L.; Pesek, J. J. (Inorg. Chem., 1971)

(untitled) - McGarrity, J. F.; Prodolliet, J.; Smyth, T. (Org. Magn. Reson., 1981)

(untitled) - Bayer, E.; Albert, K. (J. Chromatogr. A, 1984)

(untitled) - McGarrity, J. F.; Ogle, C. A.; Brich, Z.; Loosli, H. R. (J. Am. Chem. Soc., 1985)

(untitled) - Browne, D. L.; Wright, S.; Deadman, B. J.; Dunnage, S.; Baxendale, I. R.; Turner, R. M.; Ley, S. V. (Rapid Commun. Mass Spectrom., 2012)

(untitled) - Leo, G. C.; Krikava, A.; Caldwell, G. W. (Anal. Chem., 2003)

(untitled) - Potts, B. C. M.; Deese, A. J.; Stevens, G. J.; Reily, M. D.; Robertson, D. G.; Theiss, J. (J. Pharm. Biomed. Anal., 2001)

(untitled) - Teng, Q.; Ekman, D. R.; Huang, W.; Collette, T. W. (Analyst, 2012)

(untitled) - Foley, D. A.; Bez, E.; Codina, A.; Colson, K. L.; Fey, M.; Krull, R.; Piroli, D.; Zell, M. T.; Marquez, B. L. (Anal. Chem., 2014)

(untitled) - Danieli, E.; Perlo, J.; Duchateau, A. L. L.; Verzijl, G. K. M.; Litvinov, V. M.; Blümich, B.; Casanova, F. (ChemPhysChem, 2014)

(untitled) - Goldbach, M.; Danieli, E.; Perlo, J.; Kaptein, B.; Litvinov, V. M.; Blümich, B.; Casanova, F.; Duchateau, A. L. L. (Tetrahedron Lett., 2016)

(untitled) - Foley, D. A.; Dunn, A. L.; Zell, M. T. (Magn. Reson. Chem., 2016)

(untitled) - Elipe, M. V. S.; Milburn, R. R. (Magn. Reson. Chem., 2016)

(untitled) - Bart, J.; Kolkman, A. J.; Oosthoek-de Vries, A. J.; Koch, K.; Nieuwland, P. J.; Janssen, H. J. W. G.; van Bentum, J. P. J. M.; Ampt, K. A. M.; Rutjes, F. P. J. T.; Wijmenga, S. S.; Gardeniers, H. J. G. E.; Kentgens, A. P. M. (J. Am. Chem. Soc., 2009)

(untitled) - Nakakoshi, M.; Ueda, M.; Sakurai, S.; Asakura, K.; Utsumi, H.; Miyata, O.; Naito, T.; Takahashi, Y. (Magn. Reson. Chem., 2007)

(untitled) - Scheithauer, A.; Brächer, A.; Grützner, T.; Zollinger, D.; Thiel, W. R.; von Harbou, E.; Hasse, H. (Ind. Eng. Chem. Res., 2014)

(untitled) - Steinhof, O.; Scherr, G.; Hasse, H. (Magn. Reson. Chem., 2016)

(untitled) - Gomez, M. V.; Verputten, H. H. J.; Díaz-Ortız, A.; Moreno, A.; de la Hoz, A.; Velders, A. H. (Chem. Commun., 2010)

(untitled) - Gomez, M. V.; Rodríguez, A. M.; de la Hoz, A.; Jimenez-Marquez, F.; Fratila, R. M.; Barneveld, P. A.; Velders, A. H. (Anal. Chem., 2015)

(untitled) - Sans, V.; Porwol, L.; Dragone, V.; Cronin, L. (Chem. Sci., 2015)

Green Chemistry: Theory and Practice - Anastas, P. T.; Warner, J. C. (Oxford University Press, 1998)

(untitled) - Fratila, R. M.; Gomez, M. V.; Sýkora, S.; Velders, A. H. (Nat. Commun., 2014)